A human rights-based approach to compulsory treatment of young people experiencing mental disorder. Issue 1 (2nd January 2018) - Kotzmann, Jane; Bhatia, Neera; McMahon, Marilyn
ABSTRACT: The prevalence and complexity of mental disorder amongst children and young people is increasing, with a younger age of onset. Additionally, in recent decades there has been an international shift in approach to the issue of mental disorder, from that based on a medical model towards a human-rights-based approach. This shift is embodied in the Convention on the Rights of Persons with Disabilities and is purportedly adopted in Australian government legislation and policy. Using Victoria as a case study, this article explores the meaning of a human-rights-based approach to children and young people experiencing mental disorder. It considers relevant legislation, statistical data and Victorian Mental Health Tribunal cases to identify deficiencies in the Victorian legislation and its implementation. It concludes that, while a human-rights-based approach is preferable to one based on a medical model, the Victorian Mental Health Act and related legislation in other States and Territories must be amended to better realise the human rights of children and young people experiencing mental disorder.